2016
DOI: 10.1177/0734016816634783
|View full text |Cite
|
Sign up to set email alerts
|

University Policies and Programs for Crime Prevention and Awareness

Abstract: Crime on college campuses has increasingly become an area of public concern. While the Clery Act requires universities to disclose crime statistics and provide some methods of prevention, crimes on university campuses still appear to be a common problem. The purpose of this study was to examine how institutions were using the Internet to provide students with resources to promote crime prevention and awareness. Specifically, we assessed what online resources and programs institutions provided to students and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…If we are to apply Black’s (2000, p. 347) argument of “reconceptualizing the action of a person or group as the action of a social entity such as law” in line with campus policies, this speaks to the lack of collective action on sexual assault that exists within the campus culture. Campus crime legislation has been criticized for being merely symbolic in practice, demonstrable by high variability in compliance and a lack of federal funding tied to the implementation or maintenance of programs and policies focused on sexual violence on college campuses (Griffin et al, 2017; McNeal, 2007; Woodward et al, 2016). Thus, the law speaks to the need for a culture shift on a college campus through a symbiotic process of changes within both social and legal factors.…”
Section: Discussionmentioning
confidence: 99%
“…If we are to apply Black’s (2000, p. 347) argument of “reconceptualizing the action of a person or group as the action of a social entity such as law” in line with campus policies, this speaks to the lack of collective action on sexual assault that exists within the campus culture. Campus crime legislation has been criticized for being merely symbolic in practice, demonstrable by high variability in compliance and a lack of federal funding tied to the implementation or maintenance of programs and policies focused on sexual violence on college campuses (Griffin et al, 2017; McNeal, 2007; Woodward et al, 2016). Thus, the law speaks to the need for a culture shift on a college campus through a symbiotic process of changes within both social and legal factors.…”
Section: Discussionmentioning
confidence: 99%
“…Karjane and colleagues’ (2002) review of over 2,400 institutions of higher education reported differences in the ways institutions defined sexual assault, policies for reporting and responding to sexual assault, and resources provided to students. Richards’s (2016) recent study expanded upon the work of Karjane et al (2002) and found that while there have been improvements over time in institutions’ responses to sexual assault, there is still substantial variation across university responses (see also Woodward, Pelletier, Griffin, & Harrington, 2016; and see Richards & Kafonek, 2016 and Burke & Sloan, 2013 for information on state-level variations). It should be noted, however, that there is a dearth of research focusing on prevention for other forms of interpersonal violence, such as dating violence and stalking, and college students’ experiences with these types of crimes (Banyard, 2014).…”
Section: Responses To Campus Crimementioning
confidence: 99%
“…As the IHE decreases in size and residential composition, the need is amplified. Previous researchers recommend including the institution's policies, clear definitions of terminology related to SA, guides to filing campus reports and criminal charges, law enforcement contact information, and other related resources, on campus or in the community (Cleere & Lynn, 2013;Englander et al, 2016;Hayes-Smith & Hayes-Smith, 2009;Krivoshey et al, 2013;Lund & Thomas, 2015;Woodward, Pelletier, Griffin, & Harrington, 2016). It could also be helpful for IHE websites to include easily accessible information regarding the availability of on-campus staff or offices dedicated to helping, protocols to better understand what to expect when making a report to campus law enforcement, whether a confidential reporting option exists, and what to expect from the adjudication process (Amar et al, 2014;Karjane et al, 2005;Venezia & Fisher, 2013).…”
Section: Implications and Recommendationsmentioning
confidence: 99%